CD1d expression in renal cell carcinoma is associated with higher relapse rates, poorer cancer-specific and overall survival. Issue 3 (4th December 2014) - Chong, Tsung Wen; Goh, Fera Yiqian; Sim, Mei Yi; Huang, Hong Hong; Thike, Daw Aye Aye; Lim, Weng Khong; Teh, Bin Tean; Tan, Puay Hoon
Abstract : Aims: We hypothesised that CD1d expression in renal cell carcinoma (RCC) may play a role in modifying the host immune response. Our aims were to investigate the expression of CD1d and to correlate this with histopathology and clinical outcomes in a cohort study of patients with RCC. Methods: Gene expression and tissue microarray studies on a panel of RCC tissue were performed. Clinicopathological correlation was analysed using χ 2 /Fisher's exact test. Relapse-free survival, cancer-specific survival and overall survival were calculated for both CD1d high and low expressors. Survival outcomes were estimated with the Kaplan–Meier method and compared using Cox regression analysis. Results: Gene expression microarray showed significant expression of CD1d in RCC versus normal renal tissue. By immunohistochemistry, we found that CD1d expression significantly associated with tumour stage/grade, higher relapse rates, poorer cancer-specific and overall survival. Conclusions: CD1d expression on RCC correlated with aggressive disease and poorer clinical outcomes.